LncRNAs could play a vital role in osteosarcoma treatment: Inhibiting osteosarcoma progression and improving chemotherapy resistance - Xiaotong, Shi; Xiao, Li; Shiyu, Liao; Zhiguo, Bi; Chunyang, Feng; Jianguo, Liu (Frontiers in Genetics, 2023)
Osteosarcoma (OS) is one of the most common primary solid malignant tumors in orthopedics, and its main clinical treatments are surgery and chemotherapy. However, a wide surgical resection range, functional reconstruction of postoperative limbs and chemotherapy resistance are still painful for patients and challenging for orthopedists. To solve this problem completely, the discovery of new effective conservative treatments is very important. Long noncoding RNAs (lncRNAs) are RNAs that are longer than 200 nucleotides and do not encode proteins. In recent years, researchers have found that lncRNAs are closely associated with the development of osteosarcoma, which indicates that lncRNAs may play a vital role in new treatment methods for osteosarcoma. In this review, new findings of lncRNAs associated with osteosarcoma are collected, and different potential clinical applications of osteosarcoma with lncRNAs are summarized. Including downregulation of oncogenic lncRNAs, upregulation of tumor suppressive lncRNAs, and lncRNA treatment improved chemotherapy resistance. We hope these potential methods will be translated into clinical application and greatly reduce patient suffering.